Increased atmospheric CO2 combined with local climatic variation affects phenolics and spider mite populations in coffee trees - BATISTA,EUNICE R. (2021)
Abstract Modelling studies on climate change predict continuous increases in atmospheric carbon dioxide concentration [CO2] and increase in temperature. This may alter carbon-based phytochemicals such phenolics and modify plant interactions with herbivorous. We investigated the effects of enhanced [CO2] and local climatic variation on young coffee plants, Coffea arabica L. cv Catuaí vermelho IAC-144 and Obatã vermelho IAC-1669-20, cultivated in the FACE (Free-Air Carbon Dioxide Enrichment) facility under two atmospheric [CO2] conditions. Coffee leaves were evaluated for total soluble phenolics (TSP), chlorogenic (5-CQA) and caffeic (CAF) acids, diversity and population size of mites, along two dry and two rainy seasons. Elevated atmospheric CO2 (e[CO2]) significantly decreased 5-CQA in cv. Catuaí but did not affect cv. Obatã. Species richness and population size of mites in coffee leaves were not affected by e[CO2] but were strongly related to the seasonal variability of coffee leaf phenolics. In general, high levels of phenolics were negatively correlated with population size while the mite species richness were negatively correlated with 5-CQA and TSP levels. Our findings show that [CO2] enhancement affects phenolics in coffee plants differentially by cultivars, however seasonality is the key determinant of phenolics composition, mite species richness and population size.